Laboratory Measurement of Microstructure Parameters of Porous Rocks - Thanh, Luong Duy; Sprik, Rudolf (VNU Journal of Science: Mathematics - Physics; Vol 32 No 2, 2016)
Abstract: Electrokinetic phenomena are induced by the relative motion between a fluid and a solid surface and are directly related to the existence of an electric double layer between the fluid and the solid grain surface. Electrokinetics in porous media plays an important role in geophysical applications and environmental applications. Electrokinetic phenomena depend not only on fluid but also on microstructure parameters of porous media. In order to study the dependence of electrokinetics on microstructure parameters, we have measured the microstructure parameters as well as elastic moduli of 21 porous rock samples including natural rocks and artificial rocks. The experimental results are in good agreement with literature. The results show that there is a big difference in measured parameters between the natural rocks and artificial ones. Namely, the formation factors, the Poisson’s ratio of natural rocks are normally higher than those of artificial rocks. However, the porosity, the solid density and the permeability of the natural rocks are smaller than those of the artificial samples. The bulk modulus is normally higher that shear modulus for all samples. Based on the measured parameters, we will study the dependence of electrokinetic coupling coefficient on microstructure parameters of the porous media (in the upcoming paper). Keywords: Electrokinetics, streaming potential, microstructure parameters, porous media, rocks